Molecular dynamics simulations of the properties of water-methanol mixtures. Effects of force fields - Cruz Sanchez, M; Dominguez, H.; Pizio, O. (Condensed Matter Physics, 2019)
Isothermal-isobaric molecular dynamics simulations are used to examine the microscopic structure and some
properties of water-methanol liquid mixture. The TIP4P/2005 and SPC/E water models are combined with the
united atom TraPPE and the all-atom force field model for methanol. Our principal focus is to evaluate the
quality of predictions of different combinations of model force fields concerning the composition dependence
of basic properties of this system. Specifically, we explored the composition effects on density, excess molar
volume and excess entropy, as well as on the surface tension and static dielectric constant. In addition, the
structural properties are described in terms of the coordination numbers and the average number of hydrogen
bonds between molecules of constituent species. Finally, the composition dependence of self-diffusion coefficients of the species is evaluated. All theoretical predictions are tested with respect to experimental data. Моделювання методом молекулярної динамiки в iзотермiчно-iзобаричному ансамблi застосовано до дослiдження мiкроскопiчної структури та деяких властивостей рiдкої сумiшi вода-метанол. Моделi води
TIP4P/2005 i SPC/E поєднано з моделлю об’єднананих атомiв TraPPE i моделлю силових полiв всiх атомiв
для метанолу. Основною метою даної роботи є дати якiсну оцiнку передбаченням рiзних комбiнацiй модельних силових полiв стосовно концентрацiйних залежностей основних властивостей системи. Зокрема, ми дослiдили вплив концентрацiї на густину, надлишковий молярний об’єм i надлишкову ентропiю,
а також на поверхневий натяг i статичну дiелектричну сталу. Крiм цього, описано структурнi властивостi
на мовi координацiйних чисел i середнього числа водневих зв’язкiв мiж молекулами компонентiв сумiшi.
Нарештi, здiйснено оцiнку концентрацiйної залежностi коефiцiєнтiв самодифузiї компонентiв. Усi теоретичнi передбачення перевiрено по вiдношенню до експериментальних даних.